Camellia sinensis phytochemical profiling, drug-likeness, and antibacterial activity against gram-positive and gram-negative bacteria: in vitro and in silico insights - Boudou, Farouk; Belakredar, Amal; Keziz, Ahcene; Alsaeedi, Huda; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2025)
BackgroundCamellia sinensis extracts have a rich phytochemical profile and therapeutic properties. The plant contains bioactive compounds, such as catechins, flavonoids, and phenolic acids, which are associated with various health benefits, including antioxidant, anti-inflammatory, and anticancer activities.AimTo investigate the bioactive potential of a Camellia sinensis extract, particularly its antibacterial activity against Gram-positive and Gram-negative bacteria and its drug-like properties.MethodPhenolic compounds in C. sinensis extract were identified and quantified using high-performance liquid chromatography (HPLC). Its antibacterial activity was assessed against both Gram-positive (Staphylococcus aureus) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli). Drug-likeness, toxicity, and molecular properties of the identified compounds were investigated using computational approaches. Additionally, binding affinities of selected compounds were predicted via molecular docking to elucidate potential antibacterial mechanisms.ResultsHPLC identified caffeic acid (10.32 mg/g), epigallocatechin gallate (EGCG, 8.74 mg/g), syringic acid (6.21 mg/g), and quercetin (15.29 mg/g). Antibacterial activity testing revealed inhibition zones ranging from 10.62 mm for Gram-negative E. coli to 18.65 mm for Gram-positive S. aureus, comparable to gentamicin (19.42 mm). Molecular docking predicted that EGCG (−9.8 kcal/mol) was the most potent compound against Gram-negative P. aeruginosa RNase PH, followed by quercetin (−8.7 kcal/mol). Drug-likeness modeling indicated favorable profiles for most compounds, although EGCG violated Lipinski’s rule due to its molecular weight (458.4 g/mol). Density Functional Theory analysis revealed significant variations in electronic properties among the selected compounds, with quercetin exhibiting the smallest HOMO-LUMO gap (2.31 eV), suggesting high reactivity. MD simulations confirmed the stability of the EGCG-protein complex, with RMSD values (∼2.5–3.0 Å), reduced RMSF at key residues, and stable Rg (∼18–20 Å).DiscussionThe results highlight that C. sinensis is a valuable source of bioactive phenolic compounds with promising antibacterial properties against both Gram-positive and Gram-negative bacteria, particularly EGCG. Quercetin, the most abundant compound, showed better chemical stability (higher HOMO-LUMO gap), but its lower binding affinity suggests that EGCG is a more effective therapeutic candidate. Moreover, the antibacterial activity of these compounds positions them as potential alternatives to conventional antibiotics. Future research should focus on in vivo validation, structure-activity optimization, and formulation development to improve bioavailability and clinical applicability.